CLINICAL EVALUATION OF JATAMAMSI CHURNA IN THE MANAGEMENT OF ESSENTIAL HYPERTENSION - Krishna Naik, *D.Venkata; ray, Vasu; Srinivasulu, J; Ramalingeswara rao, S (International Journal of Ayurveda and Pharma Research, 2016)
In an open clinical trial 20 patients of grade-I and grade-II uncomplicated Essential Hypertension of either sex aged between 25-70 years, were given Jatamamsi Churna in a dose of 10 grams per day in two equal divided doses for a duration of 60 days. At the end of trial period their systolic blood pressure was reduced from 148.9 mm of Hg to 132.6 mm of Hg and diastolic blood pressure was reduced from 97.1 mm of Hg to 86.4 mm of Hg. Pulse pressure, mean blood pressure, and various clinical features were also significantly reduced after the therapy. No untoward effects were reported by any patient and their biochemical and Hematological parameters also remained within normal limits, both before and after the therapy. Thus trial drug i.e. Jatamamsi churna may prove an ideal drug for the management of grade-I and grade-II Essential Hypertension.